Analisis pengaruh karakteristik perusahaan terhadap manajemen modal kerja yang terdaftar di BEI - Hendi Hendi; Ellina Katherine (Universitas Internasional Batam, 2021)
Abstract The purpose of this study is to determine the effect of company characteristics on Working Capital Management in companies listed on Indonesia Stock Exchange. The conduct of this research has high hopes for companies to be aware of the influence of company characteristics on the management of company working capital. This study analyzes the effect of Leverage, Performance, Operating Cash Flow, Firm Size, Firm Age, Growth, and Firm Value on Working Capital Management. The objects chosen in this study are companies listed on the IDX. The sample in this study were companies registered before 2015, which have been audited with a full financial statement from 2015-2019. The sampling method used in this study is the purposive sampling method. Data in accordance with the criteria were processed using Eviews 10. The results showed that cash flow and leverage were significantly positive while company size and growth were significant negative. The company performance, company value, company age showed insignificant results. This shows that the company must pay attention to the characteristics of the company in managing working capital.